Secondary Ureteral Perforation by Invasive Amebiasis in a Patient with Acquired Immunodeficiency Syndrome: A Case Report - Ming-Yin Yu; Chi-Cheng Chen; Cheng-Mao Ho; Hsi-Chin Wu; Chao-Hsiang Chang; Yung-Hsiang Chen; Wen-Chi Chen (Case Reports in Nephrology)
Ureteral perforation is a rare complication of abdominal infection, especially in a patient with human immunodeficiency virus (HIV) infection. We reported a case of ureteral perforation caused by a secondary amebiasis in a patient with acquired immunodeficiency syndrome (AIDS). Following bowel perforation and immunocompromised conditions, secondary right ureteral perforation was not easily to be treated well. He was treated with percutaneous drainage initially. Definite and successful treatment by a Boari flap was delayed until his underling disease was under control.